Outcome analysis of patients with primary breast cancer initially treated at a certified academic breast unit - Heil, Jörg; Rauch, Geraldine; Marmé, Frederik; Rom, Joachim; Golatta, Michael; Junkermann, Hans; Sinn, Peter; Aulmann, Sebastian; Debus, Jürgen; Hof, Holger; Schütz, Florian; Brenner, Hermann; et al. (The breast, 2012)
Introduction: Evaluation of oncological outcome and prognostic factors of patients with primary breast cancer treated at a certified academic breast unit. Patients and methods: We prospectively collected data of 3338 patients, diagnosed with primary breast cancer between 01.01.2003 and 31.12.2010 and treated at the Breast Unit Heidelberg, Germany, in order to analyze outcome in clinical practice. We evaluated local control rate (LCR), disease-free survival (DFS), distant disease-free survival (DDFS), observed overall survival (OS) and age-adjusted relative overall survival (ROS). In addition, the impact of known prognostic factors on these outcome variables was examined in univariate and multivariate analyses. Results: Of all patients, 368 (11.0%) had carcinoma in situ (CIS) and 197 (5.9%) had bilateral cancers. For the 2970 patients with invasive cancer, of which 49 patients (1.7%) had metastastic disease at time of diagnosis, DFS, LCR, DDFS, OS and ROS at 5 years were 79.8%, 84.7%, 81.2%, 86.3%, and 89.8%, respectively. In multivariate analysis age, pT category, nodal status, hormone receptor status and grading were identified as independent prognostic factors for OS.Conclusion: Compared with recent population-based reports from Germany, more favourable patient characteristics and nominally higher survival was found among this large cohort of patients with primary breast cancer treated at a single certified breast unit.
Gesehen am 16.04.2018